2022
DOI: 10.1038/s41598-022-18815-3
|View full text |Cite
|
Sign up to set email alerts
|

Teg58, a small regulatory RNA, is involved in regulating arginine biosynthesis and biofilm formation in Staphylococcus aureus

Abstract: Staphylococcus aureus adapts to different environments by sensing and responding to diverse environmental cues. The responses are coordinately regulated by regulatory proteins, and small regulatory RNAs at the transcriptional and translational levels. Here, we characterized teg58, a SarA repressed sRNA, using ChIP-Seq and RNA-Seq analysis of a sarA mutant. Phenotypic and genetic analyses indicated that inactivation of teg58 led to reduced biofilm formation in a process that is independent of SarA, agr, PIA, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Moreover, the comparison between the Dex-BSe group and control group demonstrated that in addition to amino acids synthesis and metabolism-related pathways, DEGs were also associated with the quorum sensing and purine metabolism (Supplementary Fig. 12a ), which play important roles in S. aureus biofilm dispersion 57 , 60 . On the other hand, DEGs between the Dex group and control group were only associated with the quorum sensing and purine metabolism (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the comparison between the Dex-BSe group and control group demonstrated that in addition to amino acids synthesis and metabolism-related pathways, DEGs were also associated with the quorum sensing and purine metabolism (Supplementary Fig. 12a ), which play important roles in S. aureus biofilm dispersion 57 , 60 . On the other hand, DEGs between the Dex group and control group were only associated with the quorum sensing and purine metabolism (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4f , hierarchical clustering heatmap of biofilm-related DEGs demonstrates that the genes encoding extracellular proteases, such as sspA and sspB , were significantly upregulated in the Dex-BSe group compared with the control and Dex groups, which are involved in biofilm detachment 60 . In addition, the genes involved in arginine biosynthesis and arginine catabolism such as argF , argH , arcC , arcA , and arcD were also substantially upregulated after Dex-BSe treatment, which is supposed to inhibit the formation of biofilm and facilitate biofilm dissociation 57 . RT-PCR assay was further performed to analyze the expression levels of typical genes, verifying the RNA-seq results (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Liu et al (2022) found that arginine could promote biofilm formation in P. aeruginosa . Moreover, Adhar et al (2022) reported that the small regulatory RNA Teg58 influenced arginine biosynthesis genes (i.e., argGH encoding arginosuccinate synthetase and lyase) to reduce biofilm formation. However, Zhu et al (2007) indicated that the catabolic pathway of arginine did not play a significant role in the inhibition of biofilm formation in S. aureus .…”
Section: Discussionmentioning
confidence: 99%
“…teg58 inhibits arginine synthesis; the arginine biosynthesis gene (argGH) is upregulated in teg58 mutants. Biofilm formation is reduced in parental strains after supplementation with exogenous arginine or endogenous argGH [183]. However, teg49 does not affect biofilm formation.…”
Section: Srnasmentioning
confidence: 96%